Utilization of Pectin in the Food and Drug Industries - Ahmed, Maruf (IntechOpen, 2023)
Pectin is mostly obtained from apple pomace and citrus peels and is used to influence the textural attributes of cooked gari and fufu dough. There are a number of other underutilized sources of pectin; it can be extracted and processed from a variety of agro-industrial byproducts, including pulps, husks, hulls, peels, cactaceae, and vegetables. Pectinase enzymes are found in a wide range of organisms. This book represents and discusses the various extraction methods used to extract pectin from different sources, including such as microwave heating processes and ultrasonic treatment. The information in this book will be useful in the food and pharmaceutical industries as well as to readers seeking to learn about sources, extraction, and applications of pectin.